Natural Ventilation in Traditional Malay House A Study of Flow Pattern by an Enhanced Smoke Wire Technique - Nurizzatul Atikha, Rahmat; Kamil Khalili, Haji Abdullah; Khairun Adhani, Khairunizam (Springer, 2023)
The present work focuses on the qualitative study of flow patterns behind a traditional Malay house utilizing the smoke wire technique with enhanced control dripping and tensioner systems in a small-scaled quasi-atmospheric boundary layer wind tunnel. The controlled drip valve system is utilized to deliver a continuous smoke flow by dripping down water-based solution onto 10 nichrome wires in series. The wires are held down by the spring tensioner system to compensate for the wires’ expansion when heated to produce continuous and dense smoke lines.